Physiochemical synthesis of hydroxyapatite adsorbents from chicken and camel bone waste for removing Cd and Pb ions from polluted water - M. Nageeb Rashed; A. A. Moneam Gad; N. Magdy Fathy (Discover Water)
Abstract The utilization of waste resources to synthesize functional materials is crucial for achieving environmentally sustainable development. In this context, the current investigation aims to develop a new material using waste chicken and camel bones as adsorbents for the removal of Pb2+ and Cd2 from polluted water. The Hydroxyapatite (HA) adsorbents of chicken (HB) and camel (CB) bones were prepared via chemical treatment with NaOH, HNO3, H2O2, and ethanol, and also those followed by carbonization. The physicochemical and microscopic characteristics of the adsorbents were analyzed via SEM, XRD, FT-IR, and BET surface area analyses. Adsorption studies of Pb2+ and Cd2+ were performed in a batch style that included initial metal concentration, pH, pHpzc, solution temperature, contact time, and adsorbent dose. The results revealed that the bone chemically activated with 0.1 M NaOH had greater adsorption of Cd2+ ion (99.7% for HB and 99.89% for CB) and Pb2+ ions (99.85% for HB and 99.79% for CB) than the other activators did. Adsorption isotherms, adsorption kinetics, and thermodynamic models have been used to confirm the fit conditions that improve the adsorption technique. Maximum adsorption removal percentages for Pb2+ and Cd2+ were obtained under constant operation conditions (initial metal concentration 10 ppm, pH 6, adsorbent dose 0.05 g, contact time 30 min and solution temperature 328 K. Adsorption of Pb2+ and Cd2+ obeyed a pseudo-second-order model and fit well with the Langmuir isotherm.The metals adsorption using the prepared adsorbent was a spontaneous and exothermic process. Overall, the prepared adsorbents from chicken and camel bone waste are highly effective and promising as low-cost materials for the remediation of heavy metals-contaminated waters.